Nighttime Phone Use and Past Exposure to Cyberbullying and Their Impact on Sleep and Psychological Wellbeing in Australian Children Aged 7 to 19 Years - Stephanie Centofanti; Kurt Lushington; Andrew Wicking; Peter Wicking; Jillian Dorrian (MDPI AG, 2024)
Background: Cyberbullying and nighttime phone use are independently detrimental to sleep and psychological wellbeing, but whether in combination they might be more disruptive remains unknown. Methods: Students aged 7-19 years (N = 53,734) completed a survey measuring sleep duration, nighttime phone use, cyberbullying, and psychological distress. Results: Across stratification variables of gender (F/M) and age group (primary/secondary-school-aged children), bivariate ordered probit regression revealed that being cyberbullied and nighttime phone use were independent predictors of both increased psychological distress and obtaining <8 h sleep. Nighttime phone use was observed to moderate the relationship between cyberbullying and sleep in both primary- and secondary-school-aged girls and boys and, likewise, between cyberbullying and psychological distress, especially in secondary-school-aged boys. Notably, the moderation effect was such that the impact of nighttime phone use was lower in children who were compared with those who were not cyberbullied. This may be a ceiling effect due to the high number of cyberbullied children reporting shortened sleep and higher levels of psychological distress. Discussion: The present findings point to a possible role of nighttime phone use as a moderator of the effect of cyberbullying on sleep and psychological wellbeing. There is a need for future studies to better explore more directly the effects of cyberbullying during the nighttime.